Sistema de control interno de la gestión de inventario y la rentabilidad de la farmacia cruz azul “rosita paredes y quito” del cantón Quevedo, 2018 - Albán Guijarro, Aurora Inés (2021)
The pharmacy as an organization, goes beyond dispensing medical prescriptions for health. In business, it analyzes the environment and the competition, personnel management and unmet needs; with the purpose of being profitable. From this perspective, the Cruz Azul pharmacy "Rosita Paredes y Quito" of the Quevedo canton uses an internal control system to promote efficiency and effectiveness in the application of current standards and principles in accounting and financial matters to meet the goals set. The specific objectives include: examining the internal control system, identifying the accounting control mechanisms for inventories and measuring the level of profitability. The methodology included the systemic and analytical methods. The information was obtained through an internal control questionnaire applied to a sample of 18 people. The research proposal had a qualitative-quantitative approach, and established an evaluation to determine the impact of the internal control system of inventory management on the profitability of the Pharmacy. Among the results, the evaluation of internal control by components established a medium level of confidence and a high level of risk in terms of storage, fraud prevention procedures, documents for recording movements and inventory reports. The accounting control verified an efficiency of 100% in the replenishment of the inventory with the maximum and minimum method. In reference to inventory turnover, in 2018 it recovered the asset from drug sales in 4.47 days. Keywords: Internal control, profitability, inventory management, accounting control.